# Homework Help: Inverse function

1. Feb 20, 2008

### Master J

f(x) = ln(e^2x + e^x + 1)

I want to find the inverse of this function.

I get:

e^y=e^2x + e^x + 1

If I say then that 1=e^0, then can I say y=2x + x? Therefore, x=y/3?

2. Feb 20, 2008

### Troels

You got it right as far as taking the exponential on both sides of the equation. From there it helps to notice that:

$$e^{2x}=\left(e^x\right)^2$$

Thus converting the entire right hand side into a quadric equation:

$$e^{y}=u^2+u+1$$

where $$u=\exp(x)$$ and whilst treating $$\exp(y)$$ as a constant, solve this with respect to u

3. Feb 20, 2008

### HallsofIvy

No, you can't. e2x+ ex+ e0 is NOT equal to e2x+ x+ 0

As Troels said, you can replace ex by u and get the equation ey= u2+ u+ 1 or u2+ u+ (1- ey)= 0 and solve that with the quadratic equation.

That gives
$$u= \frac{-1\pm\sqrt{4e^y- 3}}{2}$$
You might think that gives two solutions and so there is no "inverse" function (I did at first) but since u= ex, u cannot be negative: we must take the positive root:
$$u= e^x= \frac{-1+ \sqrt{4e^y- 3}}{2}$$
so
$$x= ln(\frac{-1+ \sqrt{4e^y- 3}}{2})$$

and the inverse function is
$$f^{-1}(x)= ln(\frac{-1+ \sqrt{4e^x- 3}}{2})$$